Influence Amount Resident, Level Education And Unemployment Against Poverty In Regency Pangkajene And Island - Chaerul (Income Journal Of Economics Development, 2023)
Study This aim For know influence Amount Resident, Level Education, And Unemployment to Poverty in Pangkajene and Islands Regency. With the problem formulation, namely, is Amount resident, Level education And Unemployment influential to poverty in Regency Pangkajene And Island, Study This discussed by analyzing secondary data quantitative in the 2007-2021 time period. The data is processed again according to the needs of the analysis model used. Data source originate from Publication Body Center Statistics (BPS Pangkajene And Island, Method Study Which used is regression linear multiple with SPSS 26). Results research shows that the population variable (X1) Influential negative And Significant to poverty in Regency Pangkajene and the Islands . Level Variables Education (X2) Influential negative And No significant to Poverty in Regency Pangkajene And Islands . And the Unemployment Variable (X3) has a positive effect and No significant to poverty in Regency Pangkajene And Island.